On One Regularity Condition for Quantum Quadratic Stochastic Processes - Mukhamedov, F. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We present necessary and sufficient conditions for the validity of a regularity condition for homogeneous quantum quadratic stochastic processes defined on von Neumann algebras.